2017
DOI: 10.1016/j.vetmic.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

European surveillance of emerging pathogens associated with canine infectious respiratory disease

Abstract: Canine infectious respiratory disease (CIRD) is a major cause of morbidity in dogs worldwide, and is associated with a number of new and emerging pathogens. In a large multi-centre European study the prevalences of four key emerging CIRD pathogens; canine respiratory coronavirus (CRCoV), canine pneumovirus (CnPnV), influenza A, and Mycoplasma cynos (M. cynos); were estimated, and risk factors for exposure, infection and clinical disease were investigated. CIRD affected 66% (381/572) of the dogs studied, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 37 publications
6
57
0
Order By: Relevance
“…The New Zealand data appear to be similar to the seroprevalence of CRCoV reported from other countries, including 59.1% in Canada, 54.7% in the United States of America, 36% in the United Kingdom, and 30.3% in the Republic of Ireland (Priestnall et al 2006), as well 54% reported from a multicentre study that included 572 dogs from six European countries sampled over a period of 2 years (Mitchell et al 2017). Similar to our results, other studies found regional differences in CRCoV seroprevalence, as can be exemplified by differences between various regions in the United States of America and in the United Kingdom.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The New Zealand data appear to be similar to the seroprevalence of CRCoV reported from other countries, including 59.1% in Canada, 54.7% in the United States of America, 36% in the United Kingdom, and 30.3% in the Republic of Ireland (Priestnall et al 2006), as well 54% reported from a multicentre study that included 572 dogs from six European countries sampled over a period of 2 years (Mitchell et al 2017). Similar to our results, other studies found regional differences in CRCoV seroprevalence, as can be exemplified by differences between various regions in the United States of America and in the United Kingdom.…”
Section: Discussionsupporting
confidence: 78%
“…However affected dogs were often coinfected with several respiratory pathogens, and not all dogs with serological evidence of recent CRCoV infection developed respiratory disease, making the establishment of an aetiological link between CRCoV infection and disease challenging (Erles et al 2003;Erles and Brownlie 2005). This is similar to the situation observed for other respiratory pathogens of dogs, underscoring the fact that the aetiology of ICT is complex and factors other than exposure to a specific pathogen are likely to contribute to the outcome of infection (Erles and Brownlie 2008;Mitchell et al 2017).…”
Section: Introductionmentioning
confidence: 82%
“…CRCoV infection had been confirmed in previous studies with Japanese household dogs, and the detection rate in dogs with CIRD was 1.5% [21] and 16.0% [29], respectively. Recent studies from European countries have also reported high prevalence of CCoRV [19,28].…”
mentioning
confidence: 95%
“…zooepidemics. Although CIRD is the most common, worldwide, its etiology or epidemiology may vary across countries [6,12,18,19,21,28,31].…”
mentioning
confidence: 99%
“…Either this animal was killed in a later stage of disease, so that the causative virus was already mostly cleared in the brain, or other infectious reasons led to an inflammatory pattern, such as immune-modulated reactions. Whether PIV5 also plays a role in the disease outbreak in animals 26875 and 27020 due to a potential helper function, as it is known for kennel cough [59,60], or neuroinvasion results from an inflammation-mediated breakdown of the blood-brain barrier, remains to be elucidated. Determinants that allow the infection of cattle and the invasion in the brain need to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%